The Effectiveness of Resolving Cases of Persecution by Foreign Nationals through Restorative Justice in the Jurisdiction of the Badung Police - I Gede Yudha Kusumardika; I Made Wirya Darma (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This research aims to discuss the effectiveness of the application of restorative justice in resolving cases of persecution committed by Foreign Citizens (WNA) in the jurisdiction of the Badung Police. Bali as an international tourist destination has a high potential for friction between foreign tourists and local communities which often leads to criminal acts of persecution. The restorative justice approach regulated in the National Police Chief Regulation Number 8 of 2021 offers an alternative to resolving criminal cases outside the formal judicial mechanism by emphasizing peace, restoration of the original state, and the balance of interests of perpetrators, victims, and the community. The results of the study show that restorative justice is effectively applied, especially in cases with a mild category, because it is able to speed up the settlement of cases, reduce the burden on the court, provide direct compensation to victims, and maintain social stability and the image of Bali's tourism. An interview with IPDA I Made Aditya Riawan Putra as the Head of the Badung Police General Criminal Investigation Unit 1 emphasized that the implementation of this mechanism is only carried out if the victim agrees to a peaceful settlement and the perpetrator shows good faith. Analysis with Lawrence M. Friedman's theory of legal effectiveness shows that the substance of the law has provided a clear normative basis, the legal structure is carried out professionally by the Badung Police officers, while the legal culture of the community is relatively supportive although there is still resistance related to the perception of special treatment of foreigners. Thus, restorative justice can be seen as an effective legal instrument in bridging the gap between norms and social reality, while ensuring legal certainty and substantive justice for victims of criminal acts of persecution in the jurisdiction of the Badung Police.